Mejdalania, a new genus and three new species of Neocoelidiinae from Brazil (Insecta: Hemiptera: Cicadellidae) - Gonçalves, Clayton C. (Zootaxa, 2021)
A new Brazilian leafhopper genus of the subfamily Neocoelidiinae is proposed. Mejdalania gen. nov. is described based on three new species: Mejdalania bia sp. nov. from the state of Acre, M. longa sp. nov. from the state of Amazonas and M. unciformis sp. nov. from the state of Mato Grosso. A distribution map of Mejdalania species and an identification key for the species of the genus are provided.